High‐Resolution Imaging of Human Viruses in Liquid Droplets. Issue 37 (24th July 2021) - Jonaid, GM; Dearnaley, William J.; Casasanta, Michael A.; Kaylor, Liam; Berry, Samantha; Dukes, Madeline J.; Spilman, Michael S.; Gray, Jennifer L.; Kelly, Deborah F.
Abstract: Liquid‐phase electron microscopy (LP‐EM) is an exciting new area in the materials imaging field, providing unprecedented views of molecular processes. Time‐resolved insights from LP‐EM studies are a strong complement to the remarkable results achievable with other high‐resolution techniques. Here, the opportunities to expand LP‐EM technology beyond 2D temporal assessments and into the 3D regime are described. The results show new structures and dynamic insights of human viruses contained in minute volumes of liquid while acquired in a rapid timeframe. To develop this strategy, adeno‐associated virus (AAV) is used as a model system. AAV is a well‐known gene therapy vehicle with current applications involving drug delivery and vaccine development for COVID‐19. Improving the understanding of the physical properties of biological entities in a liquid state, as maintained in the human body, has broad societal implications for human health and disease. Abstract : The first high‐resolution view of biological assemblies contained in a liquid environment is presented. The foundation for analyzing structure and dynamics of soft materials in real‐time and in 3D is established.